2005
DOI: 10.1097/01.rli.0000170447.45577.5e
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Gadolinium-Containing Contrast-Enhancing Agents With Colorimetric Calcium Laboratory Testing

Abstract: The study demonstrates that gadopentetate dimeglumine and gadobenate dimeglumine generate no interference with colorimetric methods for calcium determination, whereas strong interference was shown for gadodiamide and gadoversetamide under clinically relevant conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The lack of an effect of gadoxetate disodium, gadoterate meglumine, and gadobutrol on the calcium assays is supported by others, as analytical interference in calcium assays has been attributed to the reduced complex stability and excess ligand in the formulation of the nonionic linear GdCAs [ 8 , 9 , 11 , 15 ]. Evidence points to the fact that gadopentetate dimeglumine, gadoterate, gadoteridol, gadobutrol, gadobenate dimeglumine, and gadoxetate disodium do not cause analytical interference in colorimetric calcium assays, regardless of which colorimetric technique was used [ 2 , 6 9 , 11 13 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The lack of an effect of gadoxetate disodium, gadoterate meglumine, and gadobutrol on the calcium assays is supported by others, as analytical interference in calcium assays has been attributed to the reduced complex stability and excess ligand in the formulation of the nonionic linear GdCAs [ 8 , 9 , 11 , 15 ]. Evidence points to the fact that gadopentetate dimeglumine, gadoterate, gadoteridol, gadobutrol, gadobenate dimeglumine, and gadoxetate disodium do not cause analytical interference in colorimetric calcium assays, regardless of which colorimetric technique was used [ 2 , 6 9 , 11 13 ].…”
Section: Discussionmentioning
confidence: 92%
“…Evidence points to the fact that gadopentetate dimeglumine, gadoterate, gadoteridol, gadobutrol, gadobenate dimeglumine, and gadoxetate disodium do not cause analytical interference in colorimetric calcium assays, regardless of which colorimetric technique was used [ 2 , 6 9 , 11 13 ]. Only nonionic linear GdCAs are relevant when considering Gd chelate binding as a mechanism in the analytical interference by CAs in laboratory blood tests [ 2 4 , 6 8 , 11 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macro minerals; sodium (Na), potassium (K), magnesium (Mg), phosphorus (P), chlorine (Cl), calcium (Ca), and micro minerals; iron (Fe), copper (Cu), and lithium (Li) will be determined using the following methods in Olympus AU 400 auto analyser and Electrolyte Analyser/ AVL machine by an appointed medical laboratory service provider (Duffy 1982 ; Khalil et al 1986 ; Burnett et al 2000 ; Löwe et al 2005 ) (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…(39) investigated the interference of gadodiamide, gadoversetamide, gadopentetate, dimeglumine, and gadoteridol on several calcium assays, and found that gadolinium contrast agents caused no interference on two arsenazo assays, one inductively coupled plasma mass spectrometry (ICP-MS) technique, one ion selective electrode assay and one ionized calcium method, whereas a negative bias was observed with three OCP methods (between −9 and −24% for gadodiamide and between −9 and −22% for gadoversetamide, respectively). Löwe et al (40) also evaluated the interference of commercially available gadolinium-containing contrast-enhancing agents with calcium measured with either an arsenazo-based colorimetric method or an OCP assay. Although gadopentetate and gadobenate did not significantly altered the concentration of calcium measured with either method, the presence of gadodiamide and gadoverset-amide caused a positive bias with arsenazo-based colorimetry and a negative one with the OCP assay.…”
Section: Analytical Interferencementioning
confidence: 99%